152 Adoptive T cell therapy targeting somatic p53 mutations. (10th December 2020) - Kim, Peter; Malekzadeh, Parisa; Vale, Nolan; Hedges, Elizabeth; Zacharakis, Nikolaos; Rosenberg, Steven
Abstract : Background: Adoptive cell therapies (ACT) directed against the products of somatic mutations in cancer cells can lead to long lasting clinical responses. We focused on ACT against shared p53 mutations to be used to potentially treat a broad range of patients with common cancers. We have built a library of anti-mutant p53 T cell receptors (TCRs) to be used for the treatment of patients with epithelial cancers in the autologous setting and as 'off-the-shelf' reagents for patients sharing the same p53 mutation and HLA. Methods: Tumor infiltrating lymphocytes (TILs) were screened for recognition of p53 mutations and were expanded as previously described. 1 For treatment of patient 4349 with metastatic breast cancer, the patient's peripheral blood T cells were retrovirally engineered to express the allogeneic anti-p53 R175H TCR. Results: We identified TILs recognizing 'hotspot' p53 mutations, such as R175H, Y220C, and R273C as well as less frequent but recurrent mutations, such as L111R, C135Y, and Q331H (table 1 ). First, we adoptively transferred TILs that included T cells reactive to a p53 mutation in an autologous manner for the treatment of patients with metastatic epithelial cancers (n=12). Except for the two patients who exhibited an objective response (RECIST), most of the patients did not respond to the therapy, possibly due to low frequencies of anti-mutant p53 cells in the infusion product, exhausted phenotype, and/or poor persistence (table 2 ). To overcome these barriers to TIL treatment, we retrovirally transduced autologous peripheral blood T cells to express an allogeneic anti-mutant p53 TCR. We engineered the HLA-A*02:01-restricted anti-p53 R175H TCR into patient 4349's lymphocytes (transduction efficiency of 64%) and saw less expression of exhaustion markers relative to the TIL infusion products (table 2 ). This patient with metastatic breast cancer was refractory to the six prior chemotherapy regimens. After the transfer of 5.3e10 cells, the patient experienced an objective partial response, showing regression by 55% of skin and mediastinal lesions for 7 months. The persistence of the infused T cells was higher than the other patients who received the TIL treatment (table 2 ). Conclusions: The library of anti-mutant p53 TCRs we have generated can potentially be used to treat 6% of all cancer patients. We are pursuing the adoptive transfer of TILs against mutant p53 naturally occurring in the tumor or TCR-engineered cells using 'off-the-shelf' receptors against mutant p53. Ethics Approval: This study was approved by the Institutional Review Board (IRB) of the NCI, and the approval numbers are as follows:Protocol 10-C-0166 (TIL treatment); Protocol 18-C-0049 (allogeneic TCR engineered T cell therapy) Reference: Lo, W., et al., Immunologic Recognition of a Shared p53 Mutated Neoantigen in a Patient with Metastatic Colorectal Cancer. Cancer Immunol Res, 2019. 7(4): p. 534–543.